Sinonasal Neoplasia – Clinicopathological Profile And Importance of Computed Tomography - Jaiganesh Sivalingam; Radha Sarawagi; Sameer Raghuwanshi; Pankaj Kumar Yadav (Journal of Clinical and Diagnostic Research, 2015)
Background: Nasal cavity and Paranasal sinus malignancies are very rare, in which maxillary sinus is the commonest, followed by ethmoid, frontal and sphenoid sinus. Computed Tomography (CT) & Magnetic Resonance Imaging (MRI) play a key role in diagnosis, staging and management of paranasal sinuses and nasal pathologies. Multiplanar imaging in CT helps better imaging of critical anatomical areas. Aim of our study was to study the incidence, clinical features, CT features and its importance in the management of sinonasal neoplasms. Materials and Methods: This prospective study was carried out in a tertiary care hospital of MP, India. Consecutive 40 histologically proven cases of sinonasal neoplasia who visited the Department of Otorhinolaryngology and Radiotherapy are included in our study. Demography and clinical features were recorded. Cases of nasal and paranasal sinus masses diagnosed on CT attending ENT and Radiotherapy OPD or admitted in the Radiotherapy ward forms the material of this study. This included patients of both sexes and all ages. Histopathological examination was asked to confirm the diagnosis made on CT. Results: There were total 40 cases of sinonasal neoplasia among which 24 were benign. Almost all the benign cases were seen in the age group <40 y with mean age of 20 y and most of the malignant cases were seen in the age group above 40 y with mean age of 55 y. In our study we found male preponderance with male female ratio of 4:1 in both benign and malignant conditions. The commonest presenting symptoms of the patients with sinonasal masses in our study was nasal obstruction (75%) and nasal discharge (67.5%) followed by nasal mass (65%), epistaxis (62.5%) and headache (60%). Angiofibroma and papilloma were the commonest benign lesions. Commonest malignant lesion was squamous cell carcinoma. Of the malignant Sinonasal tumours studied in our series, maxillary sinus was involved in 13, ethmoid sinuses and nasal cavity in 10 cases each, and frontal sinuses in 2 cases. Conclusion: Contrast enhanced computed tomography with multiplanar reconstruction is an excellent modality for imaging sinonasal masses. CT can define the character of the sinonasal mass, thus differentiating benign from malignant. CT helps better imaging of critical anatomical areas and helpful in planning treatment procedures such as surgery and radiotherapy.